Effect of different methods of polymerizing ocular prosthesis acrylic resin on a human conjunctival cell line - Freitas da Silva, Emily Vivianne [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Balera Brito, Victor Gustavo [UNESP]; Penha de Oliveira, Sandra Helena [UNESP] (Elsevier B.V., 2016)
Statement of problem. Ocular prosthesis acrylic resins should be biocompatible regardless of the polymerization method. The authors are unaware of a study that evaluated the biocompatibility of ocular prostheses. Purpose. The purpose of this in vitro study was to evaluate the cytotoxicity of different methods of polymerizing ocular prosthesis acrylic resin. This was accomplished by analyzing the cell proliferation, production of proinflammatory cytokines, and expression of extracellular matrix proteins related to tissue remodeling and repair of a human conjunctival cell line. Material and methods. Nine acrylic resin specimens were divided into 3 groups: polymerization in a water bath, by microwave, or by autopolymerization. Eluates (prepared for 72 hours) were exposed to cells for 72 hours. A medium without specimens served as negative control (non stimulated group). The tetrazolium dye MTT (3[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) assay was performed to evaluate the cytotoxic effect, and an enzyme-linked immunosorbent assay was executed for analysis of interleukin 1 beta (IL1 beta), IL6, tumor necrosis factor alpha (TNF alpha), and CCL3/MIP1 alpha production. Also, real-time reverse transcriptase (RT)-PCR was performed for analysis of mRNA expression of type IV collagen (COL IV), TGF beta, and MMP9, and data were tested using ANOVA with Bonferroni post hoc test (alpha=.05). Results. Microwave-processed resin showed slight cytotoxicity due to a significant reduction in cell proliferation and an increase in IL6 quantity. Higher levels of mRNA expression of COL IV, MMP9, and TGF beta were verified in water bath-processed resin, which were similar to those in the nonstimulated group. Conclusions. Microwave-processed resin showed a significant reduction in cell proliferation and an increase in IL6 quantity. Heat-polymerized resin exhibited a higher mRNA expression of COL IV, MMP9, and TGF beta; this result was similar to that in the nonstimulated group.